Determinants of successful driving rehabilitation training in licensed individuals with disabilities. - Yun-Ji Jeong; Jun-Su Choi; Min-Ye Jung; Jung-Ran Kim; Yoo-Gyeong Jeong; Kyoung-Young Park; Myung-Ja Kong; Kwang-Soo Lee (PLoS ONE)
Previous studies have provided that self-driving can enhance the mobility of people with disabilities and their quality of life. The National Rehabilitation Center has been providing driving rehabilitation education for people with disabilities since 1994, as part of a welfare service project aimed at guaranteeing their right to free movement. However, there is no analysis of the status and results of driving rehabilitation education and evaluations in South Korea, and research on these programs is lacking. This study aims to analyze the on-road driving rehabilitation education and evaluation results conducted by the National Rehabilitation Center from 2019 to 2021. It seeks to identify the characteristics of the prior license holders with disabilities and the factors influencing the need for additional driving rehabilitation education. Out of a total of 676 prior license holders, 532 were included in the analysis regarding the need for additional driving rehabilitation education. The results of this study indicate that women were 2.07 times more likely than men to require additional driving rehabilitation education. Conversely, the likelihood of requiring additional driving rehabilitation education was lower for those with better driving senses (0.17 times), less tension (0.46 times), and less impact from their disability (0.45 times). For prior license holders, it was found that demographic characteristics (excluding gender) or the nature of their disabilities had less significant impacts compared to the driver's response level, the type of driving license held, and the number of assistive devices used. These findings can be used for developing effective driving education programs for people with disabilities and designing strategies to enhance license acquisition rates, thereby improving their mobility rights.